Autism Spectrum Disorder Updates – Relevant Information for Early Interventionists to Consider - Allen-Meares, Paula; MacDonald, Megan; McGee, Kristin (Frontiers in Public Health, 2016)
Autism spectrum disorder (ASD) is a pervasive developmental disorder characterized by deficits in social communication skills as well as repetitive, restricted or stereotyped behaviors (1). Early interventionists are often found at the forefront of assessment, evaluation and early intervention services for children with ASD. The role of an early intervention specialist may include, assessing developmental history, providing group and individual counseling, working in partnership with families on home, school, and community environments, mobilizing school and community resources and assisting in the development of positive early intervention strategies (2, 3). The commonality amongst these roles resides in the importance of providing up-to-date, relevant information to families and children. The purpose of this review is to provide pertinent up-to-date knowledge for early interventionists to help inform practice in working with individuals with ASD, including common behavioral models of intervention.